PENGGUNAAN DAUN NANAS SEBAGAI BAHAN BAKU PEMBUATAN KERTAS SENI BERWARNA - M Djazman Addin S (Universitas Negeri makassar, 2018)
Pineapple plantations are common in Indonesia. The plantation provides a lot of waste both processed pineapple fruit and waste from the pineapple tree which is the result of post-harvest. The waste has not been optimized to obtain products that have high economic value. One of these wastes in the form of a pineapple leaf natural fiber containing 69.6 to 71% of the basic materials. The natural fibers have the potential to be processed into paper although in general the fibers used for paper materials derived from plants hard. In this research, the color art paper made from pineapple leaves using auxiliary materials NAOH, TiO2, and tapioca. Physical appearance art paper produced from this research can still compete with the art of paper on the market.